Bioimpedance Vector Analysis for Heart Failure: Should We Put It on the Agenda? - Liang, Bo; Li, Rui; Bai, Jia-Yue; Gu, Ning (Frontiers in Cardiovascular Medicine, 2021)
Heart failure is a clinical syndrome, resulting in increased intracardiac pressure and/or decreased cardiac output under rest or stress. In acute decompensated heart failure, volume assessment is essential for clinical diagnosis and management. More and more evidence shows the advantages of bioimpedance vector analysis in this issue. Here, we critically present a brief review of bioimpedance vector analysis in the prediction and management of heart failure to give a reference to clinical physicians and guideline makers.